Vexy thing on gender and liberation - Perry, Imani 1972- (Duke University Press, 2018)
Even as feminism has become increasingly central to our ideas about institutions, relationships, and everyday life, the term used to diagnose the problem-"patriarchy"-is used so loosely that it has lost its meaning. In Vexy Thing Imani Perry resurrects patriarchy as a target of critique, recentering it to contemporary discussions of feminism through a social and literary analysis of cultural artifacts from the Enlightenment to the present. Drawing on a rich array of sources-from nineteenth-century slavery court cases and historical vignettes to writings by Toni Morrison and Audre Lorde and art by Kara Walker and Wangechi Mutu-Perry shows how the figure of the patriarch emerged as part and parcel of modernity, the nation-state, the Industrial Revolution, and globalization. She also outlines how digital media and technology, neoliberalism, and the security state continue to prop up patriarchy. By exploring the past and present of patriarchy in the world we have inherited and are building for the future, Perry exposes its mechanisms of domination as a necessary precursor to dismantling it